Modelling process flows in continuous processes with radio frequency identification technique - Kvarnström, Björn; Nordqvist, Sofia (Luleå tekniska universitet, Industriell Ekonomi, 2008)
Sources of disturbances are often difficult to identify in continuous processes, as the process flows are complex. There are, however, several methods that can be used to monitor flows in complex processes and thereby to improve traceability. Radio frequency identification (RFID) technique is one such method that has been extensively used in parts production for improving traceability. The application of the technique in continuous processes is, however, sparse. The RFID technique offers the possibility to create unique tags with different characteristics that can be detected at specific locations in the process flow. With RFID, virtual batches, possible to follow through the production process, could be created in many types of continuous processes. To report the suitability of using RFID in continuous processes, experiments were conducted in a distribution chain of iron ore pellets produced at LKAB in Malmberget. In a set of experiments eight tag containers were added to the product flow to test the behavior and ability of tag readers to detect the different containers. Three characteristics were varied among the containers: shape, coating mixture and size of tag. The results from the experiments show that large tags increase the read rate, and that no significant effect on read rate could be detected when coating mixtures and shapes were shifted. A conclusion is that the RFID technique could be used to improve traceability in the distribution chain for pellets. Finally, different advantages of improved traceability in continuous processes are discussed. Godkänd; 2008; 20080915 (bjokva)